2018
DOI: 10.1038/s41598-018-33452-5
|View full text |Cite
|
Sign up to set email alerts
|

Severity of local inflammation does not impact development of fibrosis in mouse models of intestinal fibrosis

Abstract: Intestinal fibrosis is thought to be a consequence of excessive tissue repair, and constitutes a common problem in patients with Crohn’s disease (CD). While fibrosis seems to require inflammation as a prerequisite it is unclear whether the severity or persistence of inflammation influences the degree of fibrosis. Our aim was to investigate the role of sustained inflammation in fibrogenesis. For the initiation of fibrosis in vivo the models of Il10−/− spontaneous colitis, dextran sodium sulfate (DSS)-induced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The mice treated with BLM for 4 weeks exhibited signi cantly different patterns of esophageal brosis compared to those treated for 6 weeks. However, the severity of in ammation during the onset of brogenesis did not correlate with collagen deposition in the mouse model of intestinal brosis [17]. Lee et al previously reported that the lung brosis induced by BLM spontaneously decreased after more than 6 weeks [4].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mice treated with BLM for 4 weeks exhibited signi cantly different patterns of esophageal brosis compared to those treated for 6 weeks. However, the severity of in ammation during the onset of brogenesis did not correlate with collagen deposition in the mouse model of intestinal brosis [17]. Lee et al previously reported that the lung brosis induced by BLM spontaneously decreased after more than 6 weeks [4].…”
Section: Discussionmentioning
confidence: 93%
“…In our experiments, the gene expression level of IL-6 in the esophagus of BLM-treated mice was signi cantly increased compared with those of NS-treated mice. This in ammation is a pre-requisite for the initiation of brotic lesions [17].…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, the gene expression level of IL-6 in the esophagus of BLM-treated mice was significantly increased compared with those of NS-treated mice. This inflammation is a pre-requisite for the initiation of fibrotic lesions [ 19 ]. In this mouse model, BLM administration caused an increase in the thickness of gastrointestinal hyperproliferative and prefibrotic response and reduced peristaltic distance.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that more severe esophageal hyperproliferative and prefibrotic response was observed in the mice sacrificed on day 42 compared to those sacrificed on day 28. However, the severity of inflammation during the onset of fibrogenesis did not correlate with collagen deposition in another model of intestinal fibrosis [ 19 ]. Lee et al previously reported that the lung fibrosis induced by BLM spontaneously decreased after more than 6 weeks [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations support the view that inflammation is a prerequisite for the initiation of intestinal fibrosis, but neither inflammation alone nor the extent of inflammation seem to correlate well with the progression of fibrosis [ 54 , 55 ]. Once initiated, intestinal fibrogenesis may become an independent, self-perpetuating process, which would explain why the advent of highly effective anti-inflammatory biological agents seems not to have significantly reduced the incidence of fibrotic CD [ 56 ].…”
Section: Discussionmentioning
confidence: 99%